Livy : The Composition of His History - Luce, T. James (Torrey James), 1932- (Book collections on Project MUSE., 1977)
Professor Luce considers to what extent Livy may be said to have been in control of his historical material. What is the significance, the author asks, of the units by which Livy structured his history? How did he go about preparing himself to write, and what methods did he use in the course of actual composition? Did he have an interpretation of his own concerning the overall course of Roman history, and, if so, how did it affect his selection and arrangement of material?The author examines these questions largely by the means of an analysis of Books 31-45, which he compares with the work of Polybius. He then scrutinizes the design of the history as a whole, its author's attitude toward his srouces generally, and his method of composition. A final chapter considers how Livy's use of material may have been influenced by his view of change and development in Roman history, particularly with regard to the genesis and declince of the Roman national character. By examining LIvy's method of creation, Professor Luce extends our understanding of his achievement. T.J. Luce is Professor and Chairman of the Classics Department at Princeton University. Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.